Improved application of the control-of-variables strategy as a collateral benefit of inquiry-based physics education in elementary school. (February 2019) - Schalk, Lennart; Edelsbrunner, Peter A.; Deiglmayr, Anne; Schumacher, Ralph; Stern, Elsbeth
Abstract: In a quasi-experimental classroom study, we longitudinally investigated whether inquiry-based, content-focused physics instruction improves students' ability to apply the control-of-variables strategy, a domain-general experimentation skill. Twelve third grade elementary school classes ( Mdn age  = 9 years, N  = 189) were randomly assigned to receive either four different physics curriculum units (intervention) or traditional instruction (control). Experiments were frequent elements in the physics units; however, there was no explicit instruction of the control-of-variables strategy or other experimentation skills. As intended, students in the intervention classes strongly increased their conceptual physics knowledge. More importantly, students in the intervention classes also showed stronger gains in their ability to apply the control-of-variables strategy correctly in novel situations compared to students in the control classes. Thus, a high dose of experimentation had the collateral benefit of improving the transfer of the control-of-variables strategy. The study complements lab-based studies with convergent findings obtained in real classrooms. Highlights: The control-of-variables strategy (CVS) is a domain general experimentation skill. Third graders received content-focused instruction with frequent experimentation activities. This instruction never explicitly explained or mentioned the CVS. Instruction benefitted content knowledge and the ability to transfer the CVS.